Tinjauan Kualitas Layanan Manajemen Perusahaan Ritel Modern Pada PT. Asia Sanprima Jaya - Najmi Azzahwa, Siti; Eko Setyasari, Untung; Kurniadi, Yudi (POLITEKNIK LP3I, 2023)
Service quality is the level of service excellence that can be provided by service providers to meet consumer demand. To achieve a level of service quality needed a management who can plan, organize, direct, motivate and control people and work mechanisms. The management service quality focuses on meeting the needs and desires, as well as the accuracy of delivery to meet consumer expectations. The purpose of the Final Assigment is to find out the effectiveness of management service quality of Plaza Asia Mall Tasikmalaya in providing services to tenants. The research method used is descriptive research with a quantitative research approach method, that is the writer describes the results of research that were obtained from the results of data analysis in the form of number that were obtained from the field. After analyzing and discussing the problem, the writer concludes that the management service quality of modern retail company at PT. Asia Sanprima Jaya has been implemented well.